Impact of repeated military conflicts on civilian patterns of emergency medical services utilization: A retrospective cohort study - Sonkin, MD, Roman; Jaffe, PhD, Eli; Alpert, MD, Evan Avraham; Zerath, MD, PhD, Erik (American Journal of Disaster Medicine, 2022)
Objective: To assess the impact of repeated rocket attacks on a civilian population during successive military conflicts on the patterns of emergency medical services (EMS) utilization. Design: This retrospective cohort study (2008-2021) analyzed EMS data from one region of Israel characterized by intensive rocket attacks on a civilian population during four successive military conflicts. EMS activity for the periods prior to, during, and after the conflicts was compared. Data included call volume, type of calls (“medical illness,” “motor vehicle collision (MVC),” and “other-injuries”), and level of response (advanced life support (ALS) or basic life support (BLS)). Results: Compared to the Pre-Conflict period, there were statistically significant decreased volumes of calls during the 2008 (−20 percent), 2012 (−13 percent), and 2021 (−11 percent) military conflicts for “medical illness” and during the 2008 (−23 percent), 2012 (−30 percent), and 2021 (−31 percent) for “MVC.” Decreases in calls for “medical illness” were accompanied by decreased ALS dispatches (−28, −33, and −18 percent for 2008, 2012, and 2021, respectively). The number of calls returned to preconflict values during the Post-Conflict periods. No change was evidenced in numbers of calls during the 2014 military conflict. Conclusion: Military conflicts involving a civilian population were usually found to be associated with lower numbers of calls for the categories of “medical illness” and “MVC.” Less calls for “medical illness” were associated with fewer ALS dispatches. There was a rapid return of call volumes to preconflict levels shortly after a ceasefire was reached. The absence of change in calls during the 2014 conflict suggests involvement of habituation processes.